Transparency of Shariah Supervisory Board Information in Islamic Banks of Indonesia and Malaysia: The Effect of Islamic Corporate Governance - Gusrianti Gusrianti; Putri Hendra Sari (Jurnal Dinamika Akuntansi, 2023)
Purpose: This study aims to determine the level of transparency of Islamic banks in Indonesia and Malaysia by looking at the level of transparency of information related to the Sharia Supervisory Board (SSB) in Islamic banks in both countries and the influence of various characteristics of SSB on the disclosure.Method: The study covers the period 2012-2019 and the research data was obtained by conducting content analysis on the annual reports of Islamic banks.Findings: The results of the regression test show that the size and expertise of SSB have no effect on the disclosure of SSB by Islamic banks in Indonesia and Malaysia. SSB cross-membership has a positive effect on SSB-related disclosures in both countries. This study shows that the experience and knowledge gained by SSB members from their positions as SSB at various other Islamic financial institutions has a positive influence on the ability of SSB to increase the transparency of information about SSBs in Islamic banks.Novelty: This study contributes to providing empirical evidence and literature on the importance of the role of SSB in determining the level of transparency carried out by Islamic banks in the majority and most populous Islamic country in the world.